Long Haul Transportation Of Minerals In Canada?s Of Far North West - N. Gritzuk (Society for Mining, Metallurgy & Exploration, 1961)
The area of Canada with which we are here concerned consists of Yukon Territory and Northern British Columbia. Generally it lies west of the coastal mountain range and access to the sea can be gained at only selected points which are relatively few. It is served by the Alaska Highway as well as a provincial and territorial system of roads permitting transport of mining products to Whitehorse in Yukon Territory. This town it the northern terminus of the White Pass and Yukon Route, which system provides a rail service between Whitehorse and Skagway, Alaska a distance of 110 miles, and thence to Vancouver, British Columbia, by the coastal Motor Vessel C. J. Rogers, a distance of an additional 890 miles. At present the service between Vancouver, B.C. and Whitehorse, Y. T. is on a fourteen day basis. The coastal vessel, capable of carrying 3,200 tons of cargo, was specially designed and built in 1955 for handling containerized cargo and general cargo northbound, and containerized and palletized asbestos fibre, and palletized lead and zinc concentrates southbound.